EFEK CURCUMA AERUGINOSA TERHADAP PENYEMBUHAN PERINEUM IBU POSTPARTUM DI BPM AMIRUL DAN BPM PANCA MOJOKERTO - Wahyuningrum, Tria; Sadiyah, Lida Khalimatus; Khusniyati, Etik (Pusat Penelitian dan Pengabdian kepada Masyarakat FKes Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: Labor often causes injury to the birth canal. Injury in the birth canal that occurs at the base of the pelvis / perineum, vulva and vagina, cervix, uterus. The overall change genitalia tool is called involution. At this time occurred also other important changes, changes in the reproductive system including uterus, lochia,and vagina. Perineal wound care after childbirth can use traditional medicine which has long been known and in use by the people of Indonesia. One herb plants that are useful for postpartum mothers is Curcuma aeruginosa (black meeting) that have benefits to cleanse the blood after childbirth. Objective: The purpose of this study was to analyze the effectiveness of consumption of Curcuma aeruginosa extract on wound healing of the perineum on maternal postpartum Methods: The research design used a Quasi-experimental approach with Non-equivalent control group or a non-randomized control group pretest-posttest design. Observation consumption Curcuma aeruginosa extract on wound healing of the perineum on maternal postpartum. Result: Based on the statistic test it shows there is influence of curcuma aeruginosa exstract on wound healing of the perineum on maternal postpartum Conclussion: The results of this study are expected to provide a positive contribution in the field of obstetrics including: to be used as a basis for the use of herbs in the surrounding environment. Preventive efforts in the treatment of postpartum mothers. . Keywords: Curcuma aeruginosa, wound healing of the perineum.